(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
The program for the development of special coordination abilities of boys (10-11 years old) engaged in VMH-gase at the stage of initial sports training. Theoretical substantiation and experimental application of the program for the development of special coordination abilities in the VMH-Gas at the stage of initial sports training using the game method. The following methods were used during the research: theoretical analysis and generalization of literary sources, pedagogical method, method of mathematical statistics. The pedagogical experiment was conducted on the basis of Burevisnyk Junior High School in Chernivtsi, with 10-11-year-old athletes engaged in BMX-rece with coach Oleksandr Melnyk. 20 cyclists participated in the experiment, who were divided evenly into two groups of 10 people each. The game method is used in the process of physical education of cyclists for comprehensive improvement of motor activity in difficult conditions. With this, we have improved the educational and training program for the training of cyclists of the VMH-gase. The use of the game method in the training classes of young athletes showed significant differences in the increase of the result according to the indicators of special coordination between the experimental and control groups. According to the indicators of special coordination of BMX cyclists of the control group, who were engaged in the traditional program, the increase was on average from 16% to 30%. On the other hand, the increase in the result according to the indicators of coordination abilities of the experimental group increased significantly and amounted from 27% to 93%.